Drawing of "One bee's path" in the Function of Organising Children's Physical Activity in the Courtyard of the "Pcelica" Kindergarten - Marković, Marina S.; Stanišić, Irena R. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2024)
If the space where the children stay is adequately equipped (in this case painted), the children will be intrigued by the space itself, which will encourage them to engage in physical activities independently. The space encourages them to play in a safe way, to wait their turn, help each other and establish the rules of the game themselves. The aim of this work is to empirically and experimentally examine the influence of the experimental program, called "Path of a Bee" on the organization of children's physical activity in the yard of the "Bee" kindergarten. The subject of the research is the drawing of the path "Path of a bee" (experimental program) in the function of the organization of children's physical activity in the yard of the "Bee" kindergarten. 118 children from kindergarten "Bee" of  preschool institution "Nata Veljković" in Kruševac participated in the research. The action is divided into several steps, namely: determination of the part of the sidewalk for drawing the path, procurement of materials, design of the path and drawing tasks on paper, agreement on the distribution of tasks on the sidewalk, making templates, drawing the path, opening the "Path of a Bee". The instrument used in this research is the observation protocol. Through it, the organization and activities of children before (initial measurement) and after drawing the path (final measurement) in the yard of the kindergarten "Bee" were shown. When determining the initial state - free play with the current contents offered in the yard of the kindergarten, it was found that 25% of the children were independently organized in play and physical activities in the yard. By carrying out the action, i.e. drawing  "The path of a bee", the space in the kindergarten yard was enriched (footsteps, flowers, snakes, frogs, spiders, ladders, dots, hummingbirds, lines, snails, etc.), and given to the children to use as they wish. After the action, the results were obtained which state that 98% of the children played and independently organized physical activities in the yard of the kindergarten. This new environment was inviting and stimulating for the children.
Keywords: preschool age; track marking; kindergarten yard; physical activity; experimental program